Physikalische Chemie der ionisierenden Strahlung - Rolf E. Bühler (CHIMIA)
Physico-chemical aspects related to the interaction of ionizing radiation with matter are discussed. They are either specific problems of radiation, or general problems of chemical kinetics and spectroscopy, for which radiation serves as a tool. Examples are: the electron thermalization, the formation of free ions from primary ion pairs, the pion irradiation, the use of radiation-chemical systems as a reagent for specific reactions, the consequences of radical charge-transfer complexes and ionic inner complexes in chemical kinetics, and the chemistry of muonium.